The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/tme.12312
|View full text |Cite
|
Sign up to set email alerts
|

I am the 9%: Making the case for whole‐blood platelets

Abstract: Over the last 15 years, there has been a trend in the United States towards the increasing use of apheresis platelet (AP) concentrates over whole-blood-derived platelets (WBP). Although 1-h- and 24-h-corrected count increments tend to be higher with AP, this does not translate into improved haemostatic efficiency when used to prevent bleeding in haematology/oncology patients. WBP expose the recipient to more donors than apheresis products. However, recent studies have shown no significant differences in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Since the introduction of mandatory universal pathogen inactivation of all PC in 2011 [2], AP-PC and BC-PC are considered clinically equivalent. However, some differences exist between both types of PC, such as the extent of residual contaminating red blood cells (RBC), which has been shown to be considerably lower for AP-PC (0.00017-0.009 ml) compared to BC-PC (0.036-0.59 ml) [3,4,5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of mandatory universal pathogen inactivation of all PC in 2011 [2], AP-PC and BC-PC are considered clinically equivalent. However, some differences exist between both types of PC, such as the extent of residual contaminating red blood cells (RBC), which has been shown to be considerably lower for AP-PC (0.00017-0.009 ml) compared to BC-PC (0.036-0.59 ml) [3,4,5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…No anti‐D alloimmunization was reported in three studies using only apheresis PCs . RBC levels are generally two orders of magnitude higher in PCs prepared from whole blood than in apheresis PCs . They may therefore exceed the threshold required to induce anti‐D antibody production, although recent reports suggest that microparticles present in apheresis PCs may also induce RBC alloimmunization …”
Section: Discussionmentioning
confidence: 97%
“…[26][27][28] RBC levels are generally two orders of magnitude higher in PCs prepared from whole blood than in apheresis PCs. 3,29 They may therefore exceed the threshold required to induce anti-D antibody production, although recent reports suggest that microparticles present in apheresis PCs may also induce RBC alloimmunization. 30 Third, disease status probably plays a role in the higher rate of alloimmunization observed in this study than in recent studies of hematology and oncology patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nabiha Huq Saifee , 1,2 Rebecca Haley, 2 and Theresa Nester 1,2 Whole blood-derived platelet (WBDP) distribution has declined dramatically in the United States from 32.3% in 2001 to only 7.6% in 2013. 1 This national trend is not reflected in the greater Seattle area where WBDPs still account for approximately 30% of platelet (PLT) distribution.…”
mentioning
confidence: 99%
“…Data have also shown that leukoreduced WBDPs have similar hemostatic efficacy and HLA alloimmunization rate compared to leukoreduced APs and that both products carry a low risk of transfusion-related adverse events in the era of viral nucleic acid testing and bacterial testing. 2 With increased regulations and national trends of decreased donations and increased PLT usage, maintenance of an adequate PLT supply is becoming more challenging. WBDPs maximize the whole blood donor's gift and may help mitigate PLT shortages.…”
mentioning
confidence: 99%